Perceptual Experience - Hill, Christopher S. (Oxford University Press, 2022)
This book offers an account of perceptual experience-its intrinsic nature, its engagement with the world, its relations to mental states of other kinds, and its role in epistemic norms. One of the book's main claims is that perceptual experience constitutively involves representations of worldly items. A second claim is that the relevant form of representation can be explained in broadly biological terms. After defending these foundational doctrines, the book proceeds to give an account of perceptual appearances and how they are related to the objective world. Appearances turn out to be relational, viewpoint dependent properties of external objects. There is also a complementary account of how the objects that possess these properties are represented. Another major concern is the phenomenological dimension of perception. The book maintains that perceptual phenomenology can be explained reductively in terms of the representational contents of experiences, and it uses this doctrine to undercut the traditional arguments for dualism. This treatment of perceptual phenomenology is then expanded to encompass cognitive phenomenology, the phenomenology of moods and emotions, and the phenomenology of pain. The next topic is the various forms of consciousness that perceptual experience can possess. A principal aim is to show that phenomenology is metaphysically independent of these forms of consciousness, and another is to de-mystify the form known as phenomenal consciousness. The book concludes by discussing the relations of various kinds that perceptual experiences bear to higher level cognitive states, including relations of format, content, and justification or support.